Study and intervention at the working process in an universit's restaurant - Lancman, Selma; Siqueira, Adriana Rodrigues; Queiroz, Maria de Fátima Ferreira; Varela, Renata Cristina Bertolozzi (Revista de Terapia Ocupacional da Universidade de São Paulo, 2000)
This research/ intervention, carried out the University's Restaurant of the Co-ordination of Social Assistance - COSEAS/USP in the Universidade de São Paulo (USP), by combining some some methodological Procedures, such as ergonomics approach and groups of reflection conceming work, aims at transforming concrete work situation. Assuming active participation from actors of different hierarchic leveis of COSEAS, we seek to attenuate suffering work situations, to change relationships and Communications at work, to enable the participation of the workers at the work planning and to minimeze the occurrence of work-related diseases. It was our purpose, still, to discuss the reach of these methodologies and their possible contributions and limits in a concrete situation.